Virtual goods sales : new requirements for business modelling? - Hamari, Juho (2009)
Selling virtual goods is an increasingly popular revenue model for operators of social online services, examples of which are virtual worlds and social networking services. Compared to more traditional revenue models, such as time-based pricing, the revenue generation logic in virtual goods sales has a tighter interdependence with service structures, such as the rules of internal economy and game mechanics. The sold products are in interaction with the virtual environment, both of which are designed by the developers. However, the planning of business models in synergy with such service design is not currently well understood.